Evaluation of crude antigen of Dirofilaria immitis third-stage larva for detection of antibody against Wuchereria bancrofti infection by indirect ELISA. - Riyong D. (2014)
Dirofilaria immitis is an important heart worm in dogs. An immunodiagnostic test is frequently applied to use an alternative antigen from other parasites. A crude antigen from infective third stage larva (L3) of D. immitis was employed in detecting the antibody to Bancroftian filariasis in humans by indirect ELISA. It was shown that 25 cases of Bancroftian filariasis (76%) at a cut-off value of 0.230, were positive. Cross-reactivity was tested using available sera of other helminthic infections. These sera were 47% (23/49) positive. They comprised a major intestinal helminthic infection, 7 from 15 (46%) strongyloidiasis sera, none from 5 (0%) hookworm infection sera, 6 from 10 (60%) trichinosis sera, 2 from 10 (20%) cysticercosis sera and 8 from 9 (88%) gnathostomiasis sera. The mean OD of sera from Bancroftian filariasis patients was not significantly different from that of the other helminthic infections (p>0.05). In this study, crude antigen may be valuable for the serodiagnosis of Wuchereria bancrofti when subjects do not have tissue helminth infections. However, the crude antigen should be purified to obtain a better sensitivity and specificity of the test.